A method for the integration of public art in risk management frameworks: challenges and opportunities (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. The research aimed to develop an integrated and systematic method for assessing risk in contemporary public art collections. The research outlines key elements of a public-art risk-management plan. Emphasis is placed on enhancing heritage protection from natural hazards and extreme events related to climate change and, more significantly, on how such a plan can strengthen resilience in the social and historic built environment.Methodology. To develop the method, the World Heritage Historic Center of San Gimignano (Italy), comprising both medieval heritage and contemporary public art, is investigated because of its unique cultural landscape. The landscape’s contemporary elements exist as the result of several cultural initiatives: Affinità Elettive (1994), Arte all’Arte (1998-2005), and UmoCA (2011). This research highlights how the ensured survival of San Gimignano’s public art is severely conditioned by the coexistence of physical, contextual, and managerial factors (hazards and vulnerabilities).Findings. Based on case studies, the research develops indicators and criteria for vulnerability and risk analysis. Moreover, the integration of public art into, and its contribution to, general DRM frameworks is discussed. Despite the fact that public art’s values can contribute to the resilience of historic urban centers, the research reveals important challenges to overcome if public art is to be incorporated into general risk-management policies.Originality. In light of this, a risk-analysis model has been developed following international policies and frameworks, the results of which could be integrated into the general-management and conservation plan for the contemporary collections in the public space. Moreover, in recognition of the importance of social, cultural, and economic processes in the conservation of public spaces, a values assessment has been incorporated into the risk management framework.
Keywords: historic context; resilience; risk management; risk reduction; public art